2021
DOI: 10.3389/fpsyt.2021.793505
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Characteristics Analysis Using Natural Language Processing and Machine Learning Based on Phenotypes and T-Cell Subsets in Systemic Lupus Erythematosus Patients With Anxiety

Abstract: Anxiety is frequently observed in patients with systemic lupus erythematosus (SLE) and the immune system could act as a trigger for anxiety. To recognize abnormal T-cell and B-cell subsets for SLE patients with anxiety, in this study, patient disease phenotypes data from electronic lupus symptom records were extracted by using natural language processing. The Hospital Anxiety and Depression Scale (HADS) was used to distinguish patients, and 107 patients were selected to meet research requirements. Then, periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…CD27 is a member of the TNF receptor superfamily, which is involved in regulating T cells, B cells, and immunoglobulins to mediate the inflammatory response. It has been reported that CD27 may lead to anxiety or depression in patients with systemic lupus erythematosus by regulating T cells ( Gu et al, 2021 ). As a receptor of interleukin-7 (IL-7), IL7R plays a key role in immune cell development and immune system homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…CD27 is a member of the TNF receptor superfamily, which is involved in regulating T cells, B cells, and immunoglobulins to mediate the inflammatory response. It has been reported that CD27 may lead to anxiety or depression in patients with systemic lupus erythematosus by regulating T cells ( Gu et al, 2021 ). As a receptor of interleukin-7 (IL-7), IL7R plays a key role in immune cell development and immune system homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a chronic inflammatory autoimmune disease characterized by the abnormal activation of T and B lymphocytes with decreased quality of life [1,2]. SLE affects multiple organs and systems and is especially associated with neuropsychiatric problems.…”
Section: Introductionmentioning
confidence: 99%
“…2 = 0.641. Abbreviations: ASC: plasma B cell; PBMC: peripheral blood mononuclear c MAIT: mucosal-associated invariant T cell; TEMRA: effector memory CD45RA+ T cells; Th: hel T cells.…”
mentioning
confidence: 99%